Anti-Müllerian hormone in canine pyometra - Ottosson, Malin (2017)
The anti-Müllerian hormone (AMH) determines whether a foetus develops a male or female phenotype but the hormone is also produced in the adult; in the testes in males and in ovaries in females. In the ovaries, it is produced by the granulosa cells surrounding the pre-antral to small antral stage follicles. This means that the concentrations of AMH in the blood varies with the presence of these follicles. Pyometra is a common and serious disease that affects many bitches with clinical signs like depression, fever, anorexia and even peritonitis or death. Endocrinological aberrations have been suggested to play a role in the pathogenesis. The aim of the present study was to compare the concentration of AMH in bitches with pyometra with that in healthy bitches in the corresponding cyclus stage. The hypothesis was that there would be a difference in AMH concentrations between the two groups, which would indicate aberrant follicular dynamics in bitches with pyometra, possibly contributing to the pathogenesis of the disease. Blood was collected from 14 bitches suffering from pyometra and 19 control bitches. The results showed that the AMH concentration in bitches is affected by both age and weight; the older and heavier, the lower concentration of AMH. No association was detected between AMH and uterine disease. This could possibly be due to the low number of bitches but it could also indicate that the development of pyometra is not due to early aberrant follicular dynamics. However, this study does not rule out any aberrant functions in later follicular dynamics that could include cysts or persistent follicles.